1997
DOI: 10.1007/s004649900539
|View full text |Cite
|
Sign up to set email alerts
|

Utility of transesophageal echocardiography and pulmonary artery catheterization during laparoscopic assisted abdominal aortic aneurysm repair

Abstract: Insufflation increased PAD and CVP. However, volume status as suggested by EDA and PCWP did not change. These data question the reliability of hemodynamic measurements obtained from the PAC during pneumoperitoneum and suggest that TEE may be sufficient for evaluation of volume status along with the added benefit of timely detection of ventricular wall motion abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Dorsay et al found no difference in cardiac output (CO) with pneumoperitoneum, whereas McLaughlin et al reported a reduction of 30% [4,8]. More recently, when both the thermodilution technique and the transesophageal techniques were used in the same human study, the results show no significant changes in cardiac output [3,9,10]. These studies show that pulmonary capillary wedge pressure (PCWP) increases consistently with pneumoperitoneum, but both impedance measures and measures by TEE do not show a corresponding change in left ventricular volume.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Dorsay et al found no difference in cardiac output (CO) with pneumoperitoneum, whereas McLaughlin et al reported a reduction of 30% [4,8]. More recently, when both the thermodilution technique and the transesophageal techniques were used in the same human study, the results show no significant changes in cardiac output [3,9,10]. These studies show that pulmonary capillary wedge pressure (PCWP) increases consistently with pneumoperitoneum, but both impedance measures and measures by TEE do not show a corresponding change in left ventricular volume.…”
Section: Discussionmentioning
confidence: 81%
“…The effects of pneumoperitoneum have been studied extensively in both animals and humans [1,4,6,9]. Pneumoperitoneum has consistently been shown to increase mean arterial pressure, heart rate, and central venous pressure [3,4]. Decreases in cardiac output as great as 30% have been reported as well; however, most of these studies were conducted in young healthy women undergoing brief gynecologic procedures [2,7,11,12].…”
mentioning
confidence: 98%
“…Twelve intraoperative deaths were reported in 140 surgical patients in four non-comparative studies. 17,18,25,26 These numbers, however, do not lend themselves to even a crude estimation of TEE-associated risk of death because 2 of the 4 studies were case series of patients who had experienced cardiac arrest intraoperatively. 17,26…”
Section: Intraoperative Clinical Eventsmentioning
confidence: 99%
“…In the laboratory setting, preload may be assessed with echocardiography by measurement of the left ventricular end-diastolic diameter. Findings have shown echographic cardiac chamber measurements to be reliable measures of blood loss, suggesting that this technique is a good index of preload [6].…”
mentioning
confidence: 95%